2017
DOI: 10.1093/neuros/nyx559
|View full text |Cite
|
Sign up to set email alerts
|

Topical Vancomycin Reduces Surgical-Site Infections After Craniotomy: A Prospective, Controlled Study

Abstract: Topical vancomycin is a safe, effective, and cost-saving measure to prevent SSIs following craniotomy. These results have broad implications for standard of care in craniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…11 Of the 75 patients in the control group, Abdullah et al reported five SSIs and in the treatment group, they had only one infected case out of 75 patients. 14 Our findings are consistent with their findings as we had seven SSIs out of the 90 patients in the control group and no SSI in the 86 patients in the treatment group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…11 Of the 75 patients in the control group, Abdullah et al reported five SSIs and in the treatment group, they had only one infected case out of 75 patients. 14 Our findings are consistent with their findings as we had seven SSIs out of the 90 patients in the control group and no SSI in the 86 patients in the treatment group.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with the findings of Abdullah et al, Mallela et al and Ravikumar et al, where they could not find any statistically significant association between gender and SSIs. 11,12,14 The rate of surgical site infections (SSIs) in different age groups was 3.17% (2 out of 63) in the age group 50-59 years, 16% (4 out of 25) in 60 -69 years and 100% (1 out of 1) in the 70 -79 years. It was highest 16% in the age groups 60 -6 % (4 out of 25 patients).Out of the seven infected cases 2 (1.13%) were identified on 3 rd post-operative day, 4 cases on the 5 th post-operative day and 1 on the 7 th postoperative day (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…surgery; similar to the orthopaedic studies, these investigations were retrospective and noncontrolled. Among patients who underwent craniotomy, vancomycin powder use was associated with lower infection risk 5,6 , while there was no association between vancomycin powder use and infection risk in cranioplasty 7 or sternal wound infection 8 .…”
Section: Antimicrobial Prophylaxis Locally Applied Vancomycin Powdermentioning
confidence: 95%
“…67 One study found a reduction from 6 to 0.49% in a prospectively followed cohort of 355 patients. 68…”
Section: Craniotomy Infectionsmentioning
confidence: 99%